APPLICATION OF BEACON TECHNOLOGY IN OMNICHANNEL MARKETING: EUROPEAN EXPERIENCE, PROSPECTS FOR UKRAINE - BOIKO, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents key results of the European experience of using beacon technology in omnichannel marketing in the field of commerce with the aim of identifying opportunities and prospects for using this experience in Ukraine. The difference between multi-channel and omni-channel marketing is defined. For the development of the main directions of digital technologies in marketing, it is necessary to update the components included in the structure of integrated marketing communications. It has been established that under the influence of modern Internet technologies, it is necessary to redefine the various points of contact with customers, which affect the attraction of consumers and profit from the use of various omnichannels. Developing the practical aspects of the omnichannel retail strategy proposed by Y. Melantiou, it is important to consider that effective omnichannel marketing and strategic initiatives allow marketers to attract new customers and increase the level of brand loyalty. The essence, advantages and disadvantages of beacon technology are presented, the European experience of its use in the marketing activities of commercial enterprises is given, and the potential possibilities of using this technology in Ukraine are considered. The purpose of the article is to assess the level of application of beacon technologies in omnichannel marketing by retailers in order to develop a recommendation base necessary for the further effective development of omnichannel marketing in Ukraine. A scheme of interaction of beacon technologies within the framework of an omnichannel marketing strategy is proposed. A comparative analysis of multichannel and omnichannel marketing strategies is performed.Conclusions have been drawn regarding the application of omnichannel marketing in European countries and the possibilities of integrating beacon technologies into the system of omnichannel marketing in Ukraine have been determined.